Revisão conceitual de promoção da saúde e qualidade de vida na Psicologia da Saúde - Lima, Ricardo Frade de Oliveira (2018)
In Brazil in Health Psychology, the concepts of health promotion and quality of life emerged in the 1970s and since then have become part of multidisciplinary studies. This study presents a systematic empirical literature review in Health Psychology, aiming to identify how the concepts of health promotion and quality of life are defined by researchers in the area. It was also proposed to identify possible interrelations of these concepts in the production in focus and if there are differences in the conception of the concepts of health promotion and / or quality of life in different populations studied. The method used in the present study was the empirical literature review, based on the publications in journals found in the BVS-PSI database, using the following descriptors: 'health psychology', 'quality of life' and 'health promotion'. This search resulted in 102 publications for the analysis. From then on, articles were selected for the period from 2012 to 2017, in Portuguese, which resulted in 48 articles. The next criterion used was to include only journal articles according to CAPES QualiS A1, A2, B1 and B2 evaluation. The 11 selected studies were analyzed in full to identify how the concepts of quality of life and health promotion have been used in the work of Health Psychology. From the results of the analysis and the discussion, it was concluded that the studies consider that the quality of life is related to the implementation of health promotion strategies, and these strategies vary according to the population studied: in the child and elderly population, health promotion was associated with disease prevention, which would allow better quality of life. life of these individuals. The studies that approached the worker population associated health promotion as preventive measures of occupational diseases, which would improve the quality of life in the work environment. Finally, the articles of studies based on the general population, quality of life was associated with the adoption of health promotion strategies based on disease prevention and the adoption of changes in habits. It was possible to observe that although the terms quality of life and health promotion were addressed, the great majority of the studies did not present or analyzed these concepts specifically, only making a superficial approach on them. CNPq support